(untitled) (Research, Society and Development, 2021)
The regular practice of physical activity promotes health and acts to prevent various chronic diseases. Obesity is a risk factor for cardiovascular disease, hypertension, diabetes and even cancer. The use of aerobic exercise in fasting can be one of the alternatives used in the weight loss process, but it is necessary to analyze its risks in the short and long term. The objective of this work is to correlate the benefits and harms of fasting aerobic exercise on weight reduction. This is a narrative literature review. Narrative reviews are broad, suitable for describing and discussing the development or “state of the art” of a particular subject from a theoretical or conceptual point of view. Searches were performed for scientific articles published in the period 2001 to 2020 in the LILACC databases (via Virtual Health Library), MEDLINE (via PubMed), Scientific Electronic Library Online (SciELO) and Academic Google. Articles in Portuguese were selected. Gray literature was excluded: monographs, dissertations and theses. The search resulted in 388 articles, ten were selected by the researchers for the development of this review. The benefits found are increased lipid oxidation and decreased carbohydrate oxidation in different fasting periods. However, the following harms can be listed: the decrease in the availability of carbohydrates, limiting the oxidation of fatty acids; the change in body composition obtained related to the reduction of lean mass, the observed weight variations related to water loss mainly accompanied by decreased performance. Loss of fat-free mass may be related to protein catabolism. In addition to the practice of fasting physical activity in beginners, it can cause hypoglycemia.